SOSIALISASI BUDAYA MASYARAKAT YANG MERUGIKAN KESEHATAN IBU NIFAS DAN BAYI - Halu, Silfia Angela N.; Trisnawati, Reineldis Elsidianastika; Manggul, Makrina S.; Minda, Agustina (Jurnal Abdimas Bina Bangsa, 2024)
Nutritional status plays an important role in helping the healing process of perineal wounds and postpartum maternal cesarean section wounds. Poor nutritional status will have an impact on the immune system which provides protection against infectious diseases. The nutritional status of postpartum mothers can be influenced by cultural factors or public beliefs about abstinence in postpartum mothers. The Dintor community still adheres to many beliefs or cultural traditions that are related to postpartum mothers and newborns. In this village, around 13.5% of children have stunting problems. Problems regarding maternal and child nutrition, including stunting, are closely related to myths or cultural traditions of the community such as the culture of abstinence from food, which of course has nutritional content for both mothers and babies. The purpose of this activity is to increase knowledge about culture that is detrimental to the health of postpartum mothers, detrimental to the health of babies and increase public awareness of the importance of maintaining the health of postpartum mothers and babies